Pengaruh Kepercayaan Diri Terhadap Prestasi Belajar Matematika Siswa SMP Negeri 1 Buton Tengah - Herlawan Herlawan; Ernawati Jais; Hadijah Hadijah (Jurnal Akademik Pendidikan Matematika, 2022)
The formulation of the problem in this research was whether there was an effect of self-confidence on the mathematics learning achiavements of VIII grade students of SMP Negeri 1 Buton Tengah?. The purpose of this research was to determine the effect of self-confidence on mathematics learning achievement of VIII grade students of SMP Negeri 1 Buton Tengah. This research was an ex-post facto research. The population in this research were all students of VIII grade as SMP Negeri 1 Buton Tengah which consisted of 5 classes. The sample was taken as much as 20% of the total population using random sampling tachniques at SMP Negeri 1 Buton Tengah. Data collection techniques in research used a questionnaire. Based on the result of calculations using simple regression, the linear regression equation was obtained: Y = 73.108 + 0.071X. with a t value of 0.528,it was significant at 0.602>0.05. This indicuted that H0 was accepted, or H1 was rejected. This meant that there was no effect of students self-confidence on students’ mathematics learning achievements at SMP Negeri 1 Buton Tengah.